Administrative Excellence through Organizational Culture and Political Skills: Insights on Job Performance of Private HEI Leaders in Tacurong City (American Journal of Educational Leadership & Policy Studies, 2025)
Administrators’ performance is the focal point of this effective school government, building a healthy school climate and propelling the achievement of institutional goals. The impact of organizational culture and political skills on the performance of administrators in six (6) private higher education institutions (HEIs) in Tacurong City, Sultan Kudarat, Philippines is the concern of this study. Based on existing literature that ties organizational culture to employee commitment and job satisfaction and political skills to successful leadership, the study takes into consideration the two dimensions of performance: task performance and contextual performance. Utilizing a quantitative research approach, data were gathered through a survey of 272 teaching and non-teaching personnel. Findings show a significant positive relationship between organizational culture and both contextual and task performance. Likewise, political skills appeared as a decisive predictor of administrative effectiveness across both performance domains. The results emphasize the need for HEIs to cultivate a constructive organizational culture and improve the political skills of their leaders through directed leadership development initiatives. These strategies are necessary for sustaining school leadership and realizing sustainable institutional performance.